2019
DOI: 10.3390/microorganisms7090320
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Obesity among Gut Microbiota Biomarkers in African American Men with and without Diabetes

Abstract: Gut microbiota and their biomarkers may be associated with obesity. This study evaluated associations of body mass index (BMI) with circulating microbiota biomarkers in African American men (AAM) (n = 75). The main outcomes included fecal microbial community structure (16S rRNA), gut permeability biomarkers (ELISA), and short-chain fatty acids (SCFAs, metabolome analysis). These outcomes were compared between obese and non-obese men, after adjusting for age. The results showed that lipopolysaccharide-binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
0
16
0
2
Order By: Relevance
“…While the higher CD prevalence in female compared to male individuals is well established, contrasting evidence has been found regarding the relationship between CD and BMI [62]. Many studies found a positive correlation between BMI and serum SCFAs, particularly propionic, butyric, and isovaleric acid in obese patients compared to lean individuals [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…While the higher CD prevalence in female compared to male individuals is well established, contrasting evidence has been found regarding the relationship between CD and BMI [62]. Many studies found a positive correlation between BMI and serum SCFAs, particularly propionic, butyric, and isovaleric acid in obese patients compared to lean individuals [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of Stomatobaculum and Oribacterium asaccharolyticum, highlighted that Stomatobaculum encoded in its genome the cysteine desulfurase gene [41], whereas the major metabolic end product of Oribacterium asaccharolyticum was acetate [42]. Interestingly, a recent study evaluated the associations of BMI with circulating microbiota biomarkers in African American men and found that propionic and butyric SCFAs, but not acetic acid, were significant positive predictors of BMI [43]. The significant obese-associated decreases in Atopobium parvulum (Actinobacteria) and Fusobacterium nucleatum (Fusobacteria), bacterial species previously associated to Crohn's disease [44] and to tumorigenesis [45], respectively, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LPS administration to mice and healthy humans results in systemic and adipose tissue inflammation and insulin resistance, confirming that LPS affects insulin sensitivity (Mehta et al, 2010 ). Other products of microbial translocation including iFABP, a marker of gut permeability (Cox et al, 2017 ), sCD14 (Shitole et al, 2019 ), LBP (Sun et al, 2010 ; Cox et al, 2017 ; Sakura et al, 2017 ), and EndoCAb (Barengolts et al, 2019 ) are also associated with pathology in T2DM. Our data reveal a novel association of diminished metabolic endotoxemia and intestinal permeability in the presence of Ss infection.…”
Section: Discussionmentioning
confidence: 99%